SOSIALISASI PEMAHAMAN KEPADA ORANG TUA DI GKSI El-SHADDAI BOJO TENTANG PENTINGNYA PENDIDIKAN AGAMA KRISTEN - Noni Berkat Arianto Laia (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
This Community Service Implementation was held at GKSI El-Shaddai which is located in Bojo Village, Budong-budong District, Central Mamuju Regency, West Sulawesi. The methods used were field surveys, interviews, discussions, and supported by literature research. Parents at GKSI El-Shaddai are people who are in need of understanding and provision of the importance of Christian religious education in the family. Why? Referring to the results of the PkM that was carried out, the cause was the lack of understanding of parents about the use and function of PAK in the family. As a result, the children at GKSI El-Shaddai experience spiritual, character and moral decline. As a form of responsibility, the servant took the initiative to organize outreach to parents and children at GKSI El-Shaddai in order to provide them with an understanding of the nature, function and role of PAK in the family. As for the contribution of thought from the servant, namely: first, providing enlightenment to parents that PAK is an effective and powerful educational figure in educating children in truth. Second, educate parents that implementing PAK in the family is a noble responsibility from God which is given to them so that it is taught toÂ theirÂ children.